Update of the European Association of Cardiovascular Imaging (EACVI) Core Syllabus for the European Cardiovascular Magnetic Resonance Certification Exam. (22nd May 2014) - Petersen, Steffen E.; Almeida, Ana G.; Alpendurada, Francisco; Boubertakh, Redha; Bucciarelli-Ducci, Chiara; Cosyns, Bernard; Greil, Gerald F.; Karamitsos, Theodoros D.; Lancellotti, Patrizio; Stefanidis, Alexandros S.; Tann, Oliver; Westwood, Mark; et al.
Abstract: An updated version of the European Association of Cardiovascular Imaging (EACVI) Core Syllabus for the European Cardiovascular Magnetic Resonance (CMR) Certification Exam is now available online. The syllabus lists key elements of knowledge in CMR. It represents a framework for the development of training curricula and provides expected knowledge-based learning outcomes to the CMR trainees, in particular those intending to demonstrate CMR knowledge in the European CMR exam, a core requirement in the CMR certification process.